Modeling and Model Verification of the Stress-Strain State of Reinforced Polymer Concrete; Materials; Vol. 16, iss. 9 - Elemesov K. K. Kasym Koptleuevich; Sabirova L. B. Lyayla Bakhtiyarovna; Martyushev N. V. Nikita Vladimirovich; Malozemov B. V. Boris Vitaljevich; Bakhmagambetova G. B. Gulnara Bakhtiyarovna; Atanova O. V. Olga Vyacheslavovna (2023, 2023)
Title screen